Trust transfer in social media brand communities: The role of consumer engagement. (August 2018) - Liu, Linlin; Lee, Matthew K.O.; Liu, Renjing; Chen, Jiawen
Highlights: Consumers' brand trust can be transferred from their trust in other consumers and marketers in social media brand community (SMBC). Consumer engagement partially mediates the process of trust transfer. Consumer engagement in SMBC has a positive effect on brand trust. This effect is moderated by consumers' device preference to access SMBC. Abstract: Social media brand communities (SMBCs) provide firms with a potential tool to develop brand relationships. The goal of this study is to understand the value of an SMBC to that brand by examining how the community contributes to one of the central brand relationship variables—brand trust. From the perspective of trust transfer, this study considers whether and how consumer trust in a brand can be transferred from other trusted parties in the SMBC, and the mediation of consumer engagement in this process. Based on a survey of 279 SMBC participants, this study demonstrates that consumer-to-consumer trust and consumer-to-marketer trust have positive impact on consumer engagement, which subsequently influence brand trust. Also the device usage was found to moderate the impact of consumer engagement on brand trust.